Pengaruh Brand Experience, Brand Equity, dan Brand Trust terhadap Customer Satisfaction pada Skincare Wardah E-Commerce - K Rahmawati, Juhroh; Hidayat Muhmin, Andi; Tamzil, Fachmi; Faruk Sofyan, Joel (ManBiz: Journal of Management and Business, 2026)
The skincare industry in Indonesia has experienced rapid growth along with the increasing use of digital platforms and e-commerce in beauty product purchasing activities. This condition has intensified competition among skincare brands, encouraging companies to pay greater attention to consumer experience, brand value, and brand trust. This study aims to analyze the influence of Brand Experience, Brand Equity, and Brand Trust on Customer Satisfaction among Wardah skincare consumers in e-commerce. The population of this study consisted of Wardah skincare consumers in Jabodetabek aged 18-34 years. The sample consisted of 129 respondents obtained using a non-probability sampling technique with a purposive sampling method. Data were collected through online questionnaires and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results indicated that Brand Experience had a positive and significant effect on Brand Equity, Brand Trust, and Customer Satisfaction. In addition, Brand Equity had a positive and significant effect on Brand Trust and Customer Satisfaction, while Brand Trust had a positive and significant effect on Customer Satisfaction. The findings of this study indicate that Brand Trust and Brand Experience are the most influential factors in enhancing Customer Satisfaction among Wardah skincare consumers in e-commerce. Consumers’ trust in Wardah and their experience of using its products as part of their daily skincare routine contribute to Customer Satisfaction and foster long-term relationships with the Wardah brand.